Tannin determination in young coconut coir (Cocos nucifera L.) by FTIR and UV-Vis spectroscopy - Sari, Yelfira (Lembaga Layanan Pendidikan Tinggi Wilayah I Sumatra Utara (LLDikti I), 2023)
The coir of young coconut is the largest by product of coconut. Young coconut coir has no important industrial uses and until now has been incinerated or dumped without control. This is because the utilization of young coconut coir is not easy as the old one. Tannin has pharmacological activities including anti-inflammatory, antioxidant, anti-tumor This study aims to determine tannin in young coconut coir (Cocos nucifera L.) using a complementary analytical technique, Fourier Transform Infra-RedFTIR) and Ultraviolet-Visible (UV-Vis) spectroscopy. Sample of young coconut coir was obtained from the waste of bargainer at the local market. Sample was maserated using ethanol as the solvent and then was evaporated to get concentrated extract. The FTIR and UV-Vis spectra showed that the sample was indicated to contain tannin. The presence of tannin was indicated by appearance of peak at 283 nm and 326 nm in UV-Vis spectra and in the region between 1610-1445 cm-1 by FTIR. This research is an early stage in the characterization of tannin compounds from young coconut coir extract. It is expected that waste have economic value in the future.